2011
DOI: 10.1038/bjc.2011.507
|View full text |Cite
|
Sign up to set email alerts
|

Severe clinical toxicities are correlated with survival in patients with advanced renal cell carcinoma treated with sunitinib and sorafenib

Abstract: Background:In advanced renal cell carcinoma (RCC), sunitinib and sorafenib tyrosine kinase inhibitors (TKI) are associated with several clinical side effects, with no definitive established data concerning their clinical impact.Methods:From June 2006 to June 2008, main clinical TKI-induced toxicities, including digestive, cardiac, dermatologic and asthenia were retrospectively collected using the NCI-CTC version 3.0 in patients treated with TKI for an RCC.Results:The median overall survival was significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…2,7 Previous studies showed that some of these AEs have predictive value for the efficacy of sunitinib treatment. [8][9][10] The aim of this retrospective study was to systematically analyze the relationship between treatment efficacy and AEs, including the correlations with on-or off-target and the total number of AEs with treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Previous studies showed that some of these AEs have predictive value for the efficacy of sunitinib treatment. [8][9][10] The aim of this retrospective study was to systematically analyze the relationship between treatment efficacy and AEs, including the correlations with on-or off-target and the total number of AEs with treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Severe adverse events of Grades 3 and 4 have been shown to be associated with survival in patients with metastatic renal cell carcinoma (mRCC) treated with sunitinib and sorafenib, categorized as multitargeted tyrosine kinase inhibitors (1). In particular, hypertension (HT), which is one of the common adverse events associated with sunitinib, was shown to be associated with the clinical outcome in patients with mRCC treated with this drug (2).…”
Section: Introductionmentioning
confidence: 99%
“…In some cells, 24 h might be enough to sufficiently reduce Mcl-1 protein levels such that ABT alone can induce apoptosis. In these scenarios, however, there is likely to be a trade-off between drug efficacy and toxicity [31]. …”
Section: Discussionmentioning
confidence: 99%